A Systematic Review on the Application of Community of Inquiry Framework in Teaching of English as a Second/Foreign Language - Pingping Guo; Joanna Joseph Jeyaraj; Abu Bakar Razali (SAGE Open)
The CoI framework, widely recognized as a leading theoretical model for constructivist-based technology-enhanced learning, has attracted increasing attention from researchers. The abrupt shutdown caused by the pandemic has increased this interest by shifting traditional teaching to online instruction globally, even until now. Scholars in TESL/TEFL have also attempted to implement the CoI framework in teaching to optimize the online learning effects. This review aims to understand the current state of CoI studies in TESL/TEFL and explore how the CoI framework was implemented to inform future pedagogical practices. Following the PRISMA protocol, 34 articles from three scholarly article databases and other sources were included and analyzed systematically. The publication feature analysis highlighted the increasing quantity and quality of CoI publications in TESL/TEFL, with predominant contributions from scholars based in Asia. The content analysis indicated a significant prevalence of studies conducted in higher education contexts and a notable diversity in research methodologies. Blended learning, online remote/distance learning, and flipped classrooms constituted the primary learning environments to support the CoI framework. Subsequently, a detailed analysis of the CoI application was conducted, and the research findings, along with their implications for teaching, were presented.